Primary thyroid squamous cell carcinoma diagnosed with 18F-FDG PET/CT: a case report - Liao, Taiping; Long, Yongjun; Li, Lingxiao; Qi, Qinlin; Li, Li; Fu, Guoxu (Frontiers in Oncology, 2024)
Primary thyroid squamous cell carcinoma is extremely rare. We report a case of primary thyroid squamous cell carcinoma diagnosed using 18 F-FDG PET/CT. The patient presented with left axillary lymphadenopathy as the initial symptom. Fine-needle aspiration of the axillary lymph nodes indicated metastatic squamous cell carcinoma. To identify the primary tumor, the patient underwent an 18 F-FDG PET/CT scan, which revealed a mass in the thyroid and multiple enlarged lymph nodes with abnormal FDG uptake. Pathological examination of the axillary lymph nodes and thyroid biopsy confirmed the diagnosis of primary thyroid squamous cell carcinoma with lymph node metastasis.